Development of multipurpose tree lamp - Mohamad Azwan, Mohd Ghazali (2009)
This report presents about multipurpose tree lamp that usually used for decorating especially at home. This is the device which important in order to provide light, and decoration in our home. Besides that, it also has other function like hook where it used to hold something small and lightweight. The idea of the fabricate for this lamp is based on student’s creativity. The selection of suitable materials in the fabricating of this lamp is a loaded material which has ease to form, long life-span and can detain heavy load. Materials are used for the fabrication of the lamp is a round hollow steel.